Territórios de quilombos na região do Vale do Rio Jaguaribe (CE): identidades, memórias e reexistências - Silva, Samia Paula dos Santos (2022)
This research aimed to identify how the remaining quilombo residents of the communities studied build their quilombola identities, based on territorial influences, in the region of Vale do Jaguaribe in Ceará. We investigated three communities, located in the eastern region of the state of Ceará. This region presents diversity in geographic structure, so we investigated the communities that are located in mountain and coastal areas. To this end, we carried out theoretical studies aimed at our research interest, which enabled us to apprehend elements and constituent factors of the process of formation of the quilombola identity. In the field research, we used qualitative research as methodological support, using the Afro-descendant Methodology and, to collect data and information, we used several research instruments, such as: document analysis, observation and semi-structured interview. The research subjects were residents of communities of different age groups, to understand the different forms of construction of quilombola identities. The research presents an overview of the formation of quilombola communities in the studied region, highlighting the strengthening and recognition of cultural manifestations and quilombola traditions in the State of Ceará, considered as a form of resistance to ancestral values.